COMPLICATION OF PERCUTANEOUS NEPHROSTOMY (PCN) IN UPPER OBSTRUCTIVE UROPATHY: OUR ECPERIENCE - Iftikhar Ahmad; Mudassar Saeed Pansota; Muhammad Tariq et al. (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To evaluate the complications of percutaneous nephrostomy (PCN) in upper obstructive uropathy. PATIENTS AND METHODS: Total number of 200 patients of age >10 years with unilateral or bilateral obstructive uropathy in which double J stenting or retrograde catheterization could not be done or contraindicated otherwise and presented in uremia were included in the study. Patients with severe coagulopathies, liver or multisystem failure and uremia due to bladder outflow obstruction were excluded from the study. The percutaneous nephrostomy was done under ultrasound guidance by using local anesthetic. Any complications during or after procedure were noted. RESULTS: Majority of the patients 40.0% were between 26 to 40 years of age with male to female ratio was 2.6:1. The most common cause of obstructive uropathy was the stone disease (65.0%) followed by the carcinomas (18.0%). Mostly patients 56.0% were diagnosed as having mild degree of hydronephrosis and in 195 patients PCN was done successfully. Complications like bleeding and tube blockage or dislodgment was seen in 4.5% patients each while septicemia was in 3.5% patients. In our study, overall success rate was 93.0%. CONCLUSION: Percutaneous nephrostomy is a safe, quick and easy method of temporary urinary diversion in obstructive uropathy with minimal complications.